Navigating the landscape of academic prose: A corpus-driven inquiry into rhetorical preferences and their pedagogical implications for advanced L2 writers - Yang Yu; Yingying Xu; Yongkang Wu (PLoS ONE, 2026)
This study presents a pedagogically motivated inquiry into the cross-cultural rhetorical patterns of academic writing, focusing on the use of general nouns (GNs). The research was initiated in response to persistent difficulties observed among advanced L2 writers, who struggle to use GNs with appropriate nuance to establish an authoritative stance. Employing a corpus-driven methodology, the study analyzes two purpose-built corpora: the Chinese Academic Written English Corpus (CAWEC) and the Inner-Circle Affiliated Written English Corpus (ICAWEC). The findings reveal divergent rhetorical tendencies. Writers in the CAWEC show a statistically significant preference for “Research-group” (e.g., study , research ) and “Result-group” nouns (e.g., difference , results ). Their collocational patterns, marked by temporality ( current study ) and subjectivity ( our study ), are consistent with a conceptual metaphor of ACADEMIC PROGRESS IS A JOURNEY. In contrast, writers in the ICAWEC use “Example-group” (e.g., case , fact ) and certain “Discussion-group” nouns (e.g., argument ) more frequently, dominated by objectifying collocations ( the study ). These patterns suggest a spatialized argumentative strategy consistent with a conceptual metaphor of THE STUDY IS A KNOWLEDGE CONTAINER. By making these frameworks explicit, the study proposes a pedagogical model to expand L2 learners’ rhetorical repertoires and metacognitive awareness, equipping them to navigate Anglophone academic discourse.